In Search of the Holy Grail: A Specific Diagnostic Test for Rheumatic Fever - McMillan, David J.; Rafeek, Rukshan A. M.; Norton, Robert E.; Good, Michael F.; Sriprakash, Kadaba S.; Ketheesan, Natkunam (Frontiers in Cardiovascular Medicine, 2021)
Current diagnosis of Acute Rheumatic Fever and Rheumatic Heart Disease (ARF/RHD) relies on a battery of clinical observations aided by technologically advanced diagnostic tools and non-specific laboratory tests. The laboratory-based assays fall into two categories: those that (1) detect “evidence of preceding streptococcal infections” (ASOT, anti-DNAse B, isolation of the Group A Streptococcus from a throat swab) and (2) those that detect an ongoing inflammatory process (ESR and CRP). These laboratory tests are positive during any streptococcal infection and are non-specific for the diagnosis of ARF/RHD. Over the last few decades, we have accumulated considerable knowledge about streptococcal biology and the immunopathological mechanisms that contribute to the development, progression and exacerbation of ARF/RHD. Although our knowledge is incomplete and many more years will be devoted to understanding the exact molecular and cellular mechanisms involved in the spectrum of clinical manifestations of ARF/RHD, in this commentary we contend that there is sufficient understanding of the disease process that using currently available technologies it is possible to identify pathogen associated peptides and develop a specific test for ARF/RHD. It is our view that with collaboration and sharing of well-characterised serial blood samples from patients with ARF/RHD from different regions, antibody array technology and/or T-cell tetramers could be used to identify streptococcal peptides specific to ARF/RHD. The availability of an appropriate animal model for this uniquely human disease can further facilitate the determination as to whether these peptides are pathognomonic. Identification of such peptides will also facilitate testing of potential anti-streptococcal vaccines for safety and avoid potential candidates that may pre-dispose potential vaccine recipients to adverse outcomes. Such peptides can also be readily incorporated into a universally affordable point of care device for both primary and tertiary care.